Pengembangan Multimedia Interaktif Berbasis Teori Kognitif Bruner pada Mata Pelajaran Biologi Kelas X di SMA - Ananda Salsabilla Mutfi; Darmansyah; Mutiara Felicita Amsal; Khairul Alfahani (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This research was motivated by the low learning outcomes of students in Biology and the limited use of interactive learning media at SMA Negeri 2 Padang Panjang. The study aimed to develop an interactive multimedia based on Bruner's Cognitive Theory for the Ecosystem topic in Grade X Senior High School that is valid and practical for use in learning activities. This study employed a Research and Development (R&D) method using the 4D model, consisting of the Define, Design, Develop, and Disseminate stages. The product was developed using Articulate Storyline by integrating Bruner’s representation stages, namely enactive, iconic, and symbolic. The validity test was conducted by material and media experts, while the practicality test involved Grade X students of SMA Negeri 2 Padang Panjang. The results showed that the developed interactive multimedia obtained a material validity score of 4.91, categorized as very valid, and a practicality score of 83.51, categorized as very practical. Therefore, the Bruner Cognitive Theory-based interactive multimedia developed in this study is feasible to be used as a Biology learning medium to help students understand concepts in a more interesting, active, and meaningful way